Covid-19: How can sports come back? - Binney, Z. (Emory Univerity, 2020)
Remember: The author is not an infectious disease expert, a virologist, or an immunologist. He is a PhD-level epidemiologist, but he focuses on sports issues. His goal is to serve to bridge the gap between public health and sports. Here he discusses the topic sports without or with people in the stadium.